2020
DOI: 10.1021/acsanm.0c01316
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Au Nanoscale Films with Tunable Nanoporosity Prepared via Dynamic Soft Templating for Electrocatalytic Oxidation of Methanol

Abstract: We report the bottom-up synthesis of nanoporous gold (Au) thin films with monolithic morphology based on Au electrodeposition from a bicontinuous microemulsion (BME) as a dynamic soft template. Au electrodeposition occurs only at the aqueous phase of the BME, which has intertwined three-dimensional networks composed of aqueous and oil phases compartmentalized by surfactant and cosurfactant. Mutual progress in electrodeposition and dynamic change in the BME microstructure resulted in a monolithic Au nanostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…The aqueous phase of BME acted as a medium for gold electrodeposition and the intertwined structure came from the aqueous and oil phases of BME compartmentalized by surfactant and cosurfactant. The resultant film nanostructure has been controlled by adjusting the initial BME composition and by varying kinetic parameters such as deposition potential and time [53].…”
Section: Electrodepositionmentioning
confidence: 99%
“…The aqueous phase of BME acted as a medium for gold electrodeposition and the intertwined structure came from the aqueous and oil phases of BME compartmentalized by surfactant and cosurfactant. The resultant film nanostructure has been controlled by adjusting the initial BME composition and by varying kinetic parameters such as deposition potential and time [53].…”
Section: Electrodepositionmentioning
confidence: 99%
“…BME solution with a water/oil ratio of 53/47 (equally mixed BME) was prepared according to our previous report. (16) Briefly, 0.40 g of SDS, 5.00 mL of 1 M HCl aqueous solution containing 50 mM HAuCl 4 , and 510 μL of 2m2b were mixed in a glass tube. Then, the mixture solution was ultrasonicated for 15 min to fully dissolve the SDS.…”
Section: Preparation Of Bme Solutionsmentioning
confidence: 99%
“…In our previous report, we optimized the electrodeposition potential in terms of the nanostructure and concluded that excessive negative potential (−0.30 V vs Ag/AgCl) is required to form the NPGF on the sputtered Au film electrode. (16) However, the electrochemical behavior of a microelectrode is generally different from that of a macroelectrode owing to the difference in the shape of the diffusion layer. To investigate the electrodeposition potential of AuCl 4…”
Section: Investigation Of the Electrodeposition Kinetics In Equally Mixed Bmementioning
confidence: 99%
See 2 more Smart Citations